Knowledge and strategy: using configurational metaphors to explain the linkages. (19th April 2004) - Bowonder, B.; Sharma, K.J.
This paper proposes a method for linking strategy and organisational knowledge. Since metaphors induce creative visualisation they can be used for conceptualising strategic business architecture. Using examples of Exxon, Intel, Chiron and Microsoft, the concept has been illustrated.